ORGANIZAÇÃO COOPERADA E SOLIDÁRIA DE CATADORES DE MATERIAIS RECICLÁVEIS EM IJUÍ/RS - Madruga, Camila E.; Lassen, Manoel F. M.; Costa, Angela G. d. S.; Silva, Elizandra C. P. d.; Silva, Enio W. d. (Salão do Conhecimento, 2013)
Resumo